Catalyst for preparing propylene and ethylene by cracking C4 olefin as well as preparation method and application of catalyst

By using a catalyst with a core-shell structure, using the ZSM-5 molecular sieve with a composite pore structure as the core and conventional ZSM-5 molecular sieve as the shell, the problems of low conversion and selectivity of olefins in the prior art are solved, and the carbon tetraenes are significantly improved conversion rate and selectivity of propylene ethylene.

CN119425772AActive Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310959738.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14
Estimated Expiration
2043-08-01

AI Technical Summary

Technical Problem

In the existing carbon tetraolefin cracking technology, the conversion rate of olefins is low and the selectivity of the product propylene ethylene is low, especially for low-concentration carbon tetraolefin raw materials, many by-products, and poor economic performance.

Method used

The catalyst adopts a core-shell structure, the core is a ZSM-5 molecular sieve with a composite pore structure, and the shell is a conventional ZSM-5 molecular sieve. The catalyst is prepared by a two-step hydrothermal synthesis method to optimize the pore structure to improve conversion and selectivity.

Benefits of technology

The conversion rate of carbon tetraolefin and the selectivity of the product propylene ethylene are significantly improved. It is especially suitable for the propylene reaction of low-concentration carbon tetraolefin cracking, with a conversion rate of more than 63%, and the selectivity of propylene ethylene diene is greater than 80%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004371348820000101
    Figure BDA0004371348820000101
  • Figure BDA0004371348820000102
    Figure BDA0004371348820000102
  • Figure BDA0004371348820000103
    Figure BDA0004371348820000103
Patent Text Reader

Abstract

The invention discloses a catalyst for preparing propylene and ethylene by cracking C4 olefin as well as a preparation method and application of the catalyst. The catalyst is of a core-shell structure, a nuclear phase is a ZSM-5 molecular sieve with a composite pore channel structure, and a shell phase is a ZSM-5 molecular sieve; in the ZSM-5 molecular sieve with the nuclear phase composite pore channel structure, the pore volume occupied by the pore channels with the pore diameters smaller than 2 nanometers is a, the pore volume occupied by the pore channels with the pore diameters of 2-50 nanometers is b, and the pore volume occupied by the pore channels with the pore diameters larger than 50 nanometers is c; wherein b / a is in the range of 0.10 to 0.80, and c / a is in the range of 0.30 to 0.70. The catalyst is suitable for the reaction of preparing propylene and ethylene by cracking C4 olefin, and can obviously improve the conversion rate of C4 olefin and the selectivity of the product propylene and ethylene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic cracking, and specifically relates to a catalyst for cracking four carbon olefins to produce propylene and ethylene, and a preparation method and application thereof. Background Art

[0002] Propylene is an important basic organic chemical raw material, most of which comes from steam cracking and catalytic cracking units. Driven by the rapid growth in demand for polypropylene and its derivatives, the demand for propylene has continued to be strong and has grown at a relatively fast rate in recent years, so it is considered to be a product with great market potential. In order to increase propylene production, various countries have developed a variety of other methods for producing low-carbon olefins, such as the butene isomerization (OMT) process, which increases propylene production by reacting ethylene and butene; the propane dehydrogenation process (PDH) directly uses shale gas byproducts for chemical use; and the methanol to propylene technology (MTP) uses coal-based methanol to produce propylene. The new process of increasing propylene production by catalytic cracking of olefins using a large amount of C4 and C5 hydrocarbons produced by ethylene plants, FCC units and MTO units is also an important research and development direction for petrochemical companies around the world.

[0003] At present, the industrialized olefin cracking and propylene production increase processes mainly include Asahi Kasei's Omega process and UOP's OCP process. The above processes all use ZSM-5 molecular sieve as catalyst and use FCC, ethylene unit or MTO by-product mixed C4 / C5 monoolefins as raw materials. The OCP process and Omega process do not add any diluting components during the reaction process. They are characterized by high reaction space velocity, small reactor and high propylene space-time yield. The catalyst regeneration cycle is 2 to 3 days, and frequent switching and regeneration are required. Asahi Kasei's Omega process has been industrially applied in 2006. UOP combines the methanol to olefins process (MTO) and OCP, which is characterized by high propylene and ethylene yields and less by-products. CN98813467.5 discloses the use of crystalline silicate with a silicon / aluminum atomic ratio of 180 to 1000 as a catalyst at 500 to 600 ° C and a space velocity of 10 to 30 h -1 CN1284109A discloses a process for cracking C4 and / or other olefin-rich streams into propylene and other light olefins, wherein the total amount of olefins remains substantially unchanged before and after the reaction. CN1284109A discloses a process for cracking C4 and above olefins to produce propylene and ethylene, wherein the catalyst used is a hydrothermally modified ZSM-5 molecular sieve having a silicon-aluminum molar ratio greater than 200. In Example 3, the etherification C4 conversion rate is 54%, and the propylene yield is only 29%.

[0004] Currently, olefin cracking technology still has problems such as low olefin conversion rate and low yield of product propylene and ethylene. Especially in refineries, the total amount of by-product C4 is large. It is necessary to develop C4 olefin cracking catalysts with better performance to promote greater progress in olefin cracking technology. Summary of the invention

[0005] The technical problem to be solved by the present invention is that the olefin conversion rate is low and the product propylene ethylene selectivity is low in the prior art C4 olefin cracking technology, especially for low-concentration C4 olefin raw materials, there are problems such as low raw material utilization, many by-products, poor economy and product separation. The present invention provides a catalyst for preparing propylene ethylene by cracking C4 olefins and its preparation method and application. The catalyst is suitable for the reaction of preparing propylene ethylene by cracking C4 olefins, and is particularly suitable for the reaction of preparing propylene ethylene by cracking low-concentration C4 olefins in refineries, etc., and can significantly improve the C4 olefin conversion rate and the product propylene ethylene selectivity.

[0006] The first aspect of the present invention provides a catalyst for preparing propylene and ethylene by cracking C4 olefins. The catalyst is a core-shell structure, the core phase is a ZSM-5 molecular sieve with a composite pore structure, and the shell phase is a ZSM-5 molecular sieve; in the ZSM-5 molecular sieve with a core-phase composite pore structure, the pore volume occupied by the pores with a pore diameter of less than 2 nanometers is a, the pore volume occupied by the pores with a pore diameter of 2 to 50 nanometers is b, and the pore volume occupied by the pores with a pore diameter of more than 50 nanometers is c; wherein b / a is 0.10 to 0.80, preferably 0.30 to 0.80, and c / a is 0.30 to 0.70.

[0007] According to the present invention, in the catalyst, the mass ratio of the core phase to the shell phase is 1 to 5:1.

[0008] According to the present invention, in the ZSM-5 molecular sieve with a core phase composite pore structure, the pore volume occupied by pores with a pore diameter of less than 2 nanometers is 20% to 75% of the total pore volume, the pore volume occupied by pores with a pore diameter of 2 to 50 nanometers is 10% to 55% of the total pore volume, and the pore volume occupied by pores with a pore diameter of more than 50 nanometers is 6% to 30% of the total pore volume, preferably 15% to 30%.

[0009] According to the present invention, the silicon-aluminum molar ratio SiO2 / Al2O3 of the ZSM-5 molecular sieve with a core phase composite pore structure is 100-1000.

[0010] According to the present invention, in the catalyst, the shell phase ZSM-5 molecular sieve is a conventional microporous molecular sieve, and the silicon-aluminum molar ratio SiO2 / Al2O3 of the shell phase ZSM-5 molecular sieve is 100-1000.

[0011] According to the present invention, in the catalyst, in the shell phase ZSM-5 molecular sieve, the pore volume occupied by the pores with a pore diameter of less than 2 nanometers is 85% to 100% of the total pore volume; the pore volume occupied by the pores with a pore diameter of more than 50 nanometers is 0 to 15% of the total pore volume; the pore volume occupied by the pores with a pore diameter of 2 to 50 nanometers is 0 to 10% of the total pore volume. The pores with a pore diameter of more than 50 nanometers are stacked pores.

[0012] A second aspect of the present invention provides a method for preparing the above catalyst, the method comprising the following steps:

[0013] a) treating ZSM-5 molecular sieve raw powder in alkaline solution and first calcining to obtain a precursor;

[0014] b) mixing the template, aluminum source, silicon source, alkali source and the precursor in step a), performing hydrothermal crystallization, performing a second calcination, then performing ammonium exchange, and performing a third calcination to obtain the catalyst.

[0015] According to the present invention, the alkali in step a) includes at least one of sodium hydroxide and sodium carbonate. The mass concentration of the alkali solution is 5% to 10%. The temperature of the treatment in the alkali solution is 60 to 100° C., preferably 60 to 90° C. The treatment time in the alkali solution is 2 to 4 hours. The alkali solution treatment can be carried out under stirring. After the alkali solution treatment, the solid is filtered and then dried. The drying temperature is 80 to 120° C. and the time is 8 to 10 hours.

[0016] According to the present invention, the conditions of the first calcination in step a) are: temperature 500-600° C., time 4-8 hours. The precursor obtained after the first calcination is a multi-level pore ZSM-5 molecular sieve.

[0017] According to the present invention, in step a), the ZSM-5 molecular sieve raw powder can be conventional commercially available ZSM-5 molecular sieve or homemade. The preparation method of the ZSM-5 molecular sieve raw powder comprises the steps of uniformly mixing the template, aluminum source, silicon source, and alkali source, hydrothermally crystallizing, and calcining to obtain the ZSM-5 molecular sieve raw powder.

[0018] According to the present invention, in the preparation method of the ZSM-5 molecular sieve raw powder, the template includes at least one of tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide and tetrapropylammonium hydroxide. The aluminum source includes at least one of aluminum nitrate, aluminum sulfate and sodium aluminate. The silicon source includes at least one of water glass, silica sol and tetraethyl orthosilicate. The alkali source includes at least one of sodium hydroxide and potassium hydroxide. The template is NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 + :Al2O3:SiO2:OH - : H2O = 0.1-0.5: 0.001-0.01: 1: 0.1-0.4: 5-10. The temperature of the hydrothermal crystallization is 80-200°C, and the crystallization time is 10-50h. The hydrothermal crystallization equipment is preferably an autoclave. The pressure of the autoclave is not particularly limited and is autogenous pressure. After hydrothermal crystallization, water washing and drying are performed. The drying temperature is 60-100°C and the time is 10-20 hours. The roasting temperature is 400-500°C and the time is 5-10h.

[0019] According to the present invention, in step b), the template includes at least one of tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide and tetrapropylammonium hydroxide. The aluminum source includes at least one of aluminum nitrate, aluminum sulfate and sodium aluminate. The silicon source includes at least one of water glass, silica sol and tetraethyl orthosilicate. The alkali source includes at least one of sodium hydroxide and potassium hydroxide. The template is NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 + :Al2O3:SiO2:OH - : H2O=0.1~0.5: 0.001~0.01: 1: 0.1~0.4: 5~10.

[0020] According to the present invention, in step b), the temperature of the hydrothermal crystallization is 80-200°C, and the crystallization time is 10-50h. The hydrothermal crystallization equipment is preferably an autoclave. The pressure of the autoclave is not particularly limited and is autogenous pressure. After hydrothermal crystallization, water washing and drying are performed. The drying temperature is 80-120°C and the time is 8-12 hours. The temperature of the second calcination is 500-600°C and the time is 4-8h. The second calcination product is the core-shell ZSM-5 molecular sieve raw powder.

[0021] According to the present invention, in the catalyst of step b), the mass ratio of the core phase to the shell phase is 1 to 5:1.

[0022] According to the present invention, the ammonium exchange in step b) can be carried out by conventional methods. Preferably, the exchange is carried out at 80-90° C. with a 5-10 wt % aqueous ammonium salt solution. The ammonium salt is preferably ammonium nitrate.

[0023] According to the present invention, the temperature of the third calcination in step b) is 500-600° C. and the time is 4-8 hours.

[0024] According to the present invention, the catalyst in step b) is a core-shell structure, the core phase is a ZSM-5 molecular sieve with a composite pore structure, and the shell phase is a ZSM-5 molecular sieve. In the ZSM-5 molecular sieve with a core-phase composite pore structure, the pore volume occupied by the pores with a pore diameter of less than 2 nanometers is a, the pore volume occupied by the pores with a pore diameter of 2 to 50 nanometers is b, and the pore volume occupied by the pores with a pore diameter of more than 50 nanometers is c; wherein b / a is 0.10 to 0.80, preferably 0.30 to 0.80, and c / a is 0.30 to 0.70.

[0025] According to the present invention, in the catalyst of step b), in the ZSM-5 molecular sieve with a core phase composite pore structure, the pore volume occupied by pores with a pore diameter of less than 2 nanometers is 20% to 75% of the total pore volume, the pore volume occupied by pores with a pore diameter of 2 to 50 nanometers is 10% to 55% of the total pore volume, and the pore volume occupied by pores with a pore diameter of more than 50 nanometers is 6% to 30% of the total pore volume, preferably 15% to 30%.

[0026] The third aspect of the present invention provides an application of the above catalyst or the catalyst prepared by the above method in the cracking reaction of C4 olefins to produce propylene and ethylene.

[0027] According to the present invention, the application is a reaction of cracking low-concentration C4 olefins to produce propylene and ethylene. The low-concentration C4 olefin raw material comes from C4 hydrocarbons in a refinery. In the C4 hydrocarbons, the mass concentration of C4 olefins is 30% to 50%. Further, the C4 hydrocarbons are C4 mixed hydrocarbons. The C4 mixed hydrocarbons include at least one C4 olefin and at least one C4 alkane. In the C4 hydrocarbons, the mass concentration of C4 olefins is 30% to 50%, and the mass concentration of C4 alkane is 50% to 70%.

[0028] According to the present invention, the reaction conditions are as follows: the reaction temperature is 500-600°C, preferably 520-580°C, the reaction pressure is 0-1.0 MPa, preferably 0.03-0.8 MPa, and the weight space velocity of C4 hydrocarbons is 1-30 h -1 , preferably 2 to 20 hours -1 .

[0029] Compared with the prior art, the present invention has significant advantages and outstanding effects, mainly including:

[0030] (1) In the present invention, the catalyst adopts a core-shell structure catalyst, the core is a ZSM-5 molecular sieve with a composite pore structure, and the shell is a conventional ZSM-5 molecular sieve. The inventors have found through research that in the ZSM-5 molecular sieve with a composite pore structure, when the pore volume ratio of mesopores to micropores is 0.10-0.80, and the pore volume ratio of macropores to micropores is 0.30-0.70, the core-shell structure catalyst of the present invention is applied to the reaction of cracking C4 olefins to produce propylene and ethylene, especially the reaction of cracking low-concentration C4 olefins to produce propylene, which can significantly improve the conversion rate of C4 olefins and the selectivity of the product propylene and ethylene.

[0031] (2) In the present invention, the preparation method of the catalyst adopts a two-step hydrothermal synthesis method to prepare a core-shell catalyst, firstly treating and modifying the ZSM-5 molecular sieve raw powder with an alkaline solution to obtain a ZSM-5 molecular sieve with a composite pore structure. The molecular sieve raw powder with the composite pore structure is evenly dispersed in the raw material mixture, and hydrothermally crystallized for a second time to finally obtain a molecular sieve catalyst with a core-shell structure. The core-shell structure catalyst prepared by the present invention is applied to the reaction of cracking C4 olefins to produce propylene and ethylene, especially the reaction of cracking low-concentration C4 olefins to produce propylene, and can significantly improve the conversion rate of C4 olefins and the selectivity of the product propylene and ethylene.

[0032] (3) In the present invention, the application of the catalyst for preparing propylene and ethylene by cracking C4 olefins can significantly improve the conversion rate of C4 olefins and the selectivity of the products propylene and ethylene by optimizing the reaction process conditions and using the core-shell structure catalyst with a composite pore structure as the core phase of the present invention, and is particularly suitable for the reaction of preparing propylene by cracking low-concentration C4 olefins. The conversion rate of the raw material low-concentration C4 olefins can reach more than 63%, and the selectivity of the products propylene, ethylene and diene is greater than 80%, achieving good technical effects. DETAILED DESCRIPTION

[0033] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited by the examples.

[0034] In the present invention, the pore distribution measurement is performed on a TriStar 3000 physical adsorption instrument. After vacuum treatment at 300°C for 3 hours, the sample is placed in a tester and liquid nitrogen is added for testing, and the Barret-Joyner-Halenda (BJH) model is used to calculate the sample pore distribution.

[0035] In the context of this specification, the following formula is used for calculation:

[0036] C4 olefin conversion rate (wt%) = (1-C4 olefin mass in product / C4 olefin mass in raw material) × 100%;

[0037] Propylene selectivity (wt%) = mass of propylene generated in the product / (mass of C4 olefins in the feedstock - mass of C4 olefins in the product) × 100%;

[0038] Ethylene selectivity (wt%) = mass of ethylene generated in the product / (mass of C4 olefins in the feedstock - mass of C4 olefins in the product) × 100%.

[0039] In each case, the C4 raw material comes from the mixed C4 in the refinery, and the raw material composition is shown in Table 2.

[0040] Example 1

[0041] Step a)

[0042] Preparation of ZSM-5 molecular sieve raw powder:

[0043] Tetramethylammonium bromide was used as the template, aluminum nitrate was used as the aluminum source, silica sol was used as the silicon source, sodium hydroxide was used as the alkali source, and the template was NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - :H2O=0.1:0.005:1:0.3:6. The above raw materials are mixed and stirred evenly until they are in an emulsion state, then transferred into an autoclave and crystallized at 120°C for 35 hours. The synthesized product is washed with water, dried at 60°C for 20 hours, and calcined at 500°C for 5 hours to obtain ZSM-5 molecular sieve raw powder.

[0044] Precursor preparation:

[0045] The ZSM-5 molecular sieve raw powder was dispersed in a 5% sodium carbonate solution, stirred at 80° C. for 3 hours, filtered, dried at 120° C. for 8 hours, and calcined at 600° C. for 4 hours to obtain a precursor multi-level pore ZSM-5 molecular sieve.

[0046] Step b)

[0047] The materials were re-formulated with the same composition as the above-mentioned synthetic molecular sieve raw material powder, but the total material was reduced to 50%. Tetramethylammonium bromide was used as the template, aluminum nitrate was used as the aluminum source, silica sol was used as the silicon source, sodium hydroxide was used as the alkali source, and the template was NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - :H2O=0.1:0.005:1:0.3:6, mix the above raw materials and add into the precursor prepared in step a), then stir evenly until it becomes an emulsion and transfer into an autoclave, crystallize at 150°C for 10 hours, wash the synthesized product with water, dry it at 80°C for 12 hours, and calcine it at 600°C for 4 hours to obtain the desired core-shell ZSM-5 molecular sieve raw powder.

[0048] The core-shell ZSM-5 molecular sieve raw powder is exchanged with a 10% ammonium nitrate aqueous solution at 90°C, washed and dried, and then calcined at 500°C for 8 hours, pressed into tablets, and sieved to obtain a catalyst for the cracking of C4 olefins to propylene and ethylene. The pore distribution of the catalyst core phase molecular sieve is shown in Table 1. The pore distribution of the catalyst shell phase molecular sieve is: the pore volume occupied by the pores with a pore diameter of less than 2 nanometers is 87% of the total pore volume, the pore volume occupied by the pores with a pore diameter of 2 to 50 nanometers is 3% of the total pore volume, and the pore volume occupied by the pores with a pore diameter of more than 50 nanometers is 10% of the total pore volume. The mass ratio of the catalyst core phase to the shell phase is 2:1.

[0049] The fixed-bed catalytic reaction device was used to evaluate the activity of the prepared catalyst in the cracking of C4 olefins to produce propylene and ethylene. The process conditions used in the investigation were: reaction temperature of 530°C, reaction pressure of 0.02MPa, and C4 hydrocarbon weight space velocity of 15h -1 The evaluation results are shown in Table 3.

[0050] Example 2

[0051] Step a)

[0052] Preparation of ZSM-5 molecular sieve raw powder:

[0053] Tetrapropylammonium hydroxide was used as the template, aluminum sulfate was used as the aluminum source, ethyl orthosilicate was used as the silicon source, potassium hydroxide was used as the alkali source, and the template was NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - :H2O=0.5:0.001:1:0.4:10. The above raw materials are mixed and stirred evenly until they are in an emulsion state, then transferred into an autoclave and crystallized at 150°C for 25 hours. The synthesized product is washed with water, dried at 80°C for 15 hours, and calcined at 400°C for 10 hours to obtain ZSM-5 molecular sieve raw powder.

[0054] Precursor preparation:

[0055] The ZSM-5 molecular sieve raw powder was dispersed in 8% sodium hydroxide solution, stirred at 60° C. for 4 hours, filtered, dried at 80° C. for 10 hours, and calcined at 500° C. for 8 hours to obtain a precursor multi-level pore ZSM-5 molecular sieve.

[0056] Step b)

[0057] Re-formulate the materials in the same proportion as the above-mentioned synthetic molecular sieve raw material composition and total material. Use tetrapropylammonium hydroxide as the template, aluminum sulfate as the aluminum source, ethyl orthosilicate as the silicon source, potassium hydroxide as the alkali source, and the template agent as NH4 +The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - :H2O=0.5:0.001:1:0.4:10, mix the above raw materials and add into the precursor prepared in step a), then stir evenly until it becomes an emulsion and transfer into an autoclave, crystallize at 150°C for 25 hours, wash the synthesized product with water, dry it at 120°C for 8 hours, and calcine it at 550°C for 6 hours to obtain the desired core-shell ZSM-5 molecular sieve raw powder.

[0058] The core-shell ZSM-5 molecular sieve raw powder is exchanged with a 5% ammonium nitrate aqueous solution at 90°C, washed and dried, and then calcined at 600°C for 4 hours, pressed into tablets, and sieved to obtain a catalyst for cracking carbon four olefins to produce propylene and ethylene. The pore distribution of the catalyst core phase molecular sieve is shown in Table 1. The pore distribution of the catalyst shell phase molecular sieve is: the pore volume occupied by pores with a pore diameter of less than 2 nanometers is 92% of the total pore volume, the pore volume occupied by pores with a pore diameter of 2 to 50 nanometers is 3% of the total pore volume, and the pore volume occupied by pores with a pore diameter of more than 50 nanometers is 5% of the total pore volume. The mass ratio of the catalyst core phase to the shell phase is 1:1.

[0059] The fixed-bed catalytic reaction device was used to evaluate the activity of the prepared catalyst in the cracking of C4 olefins to produce propylene and ethylene. The process conditions used in the investigation were: reaction temperature of 530°C, reaction pressure of 0.02MPa, and C4 hydrocarbon weight space velocity of 15h -1 The evaluation results are shown in Table 3.

[0060] Example 3

[0061] Step a)

[0062] Preparation of ZSM-5 molecular sieve raw powder:

[0063] Tetraethylammonium bromide was used as template, sodium aluminate as aluminum source, water glass as silicon source, sodium hydroxide as alkali source, and NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - :H2O=0.3:0.01:1:0.1:10. The above raw materials are mixed and stirred evenly until they are in an emulsion state, then transferred into an autoclave and crystallized at 180°C for 30 hours. The synthesized product is washed with water, dried at 100°C for 10 hours, and calcined at 400°C for 10 hours to obtain ZSM-5 molecular sieve raw powder.

[0064] Precursor preparation:

[0065] The ZSM-5 molecular sieve raw powder was dispersed in a 10% sodium carbonate solution, stirred at 90° C. for 2 hours, filtered, dried at 100° C. for 8 hours, and calcined at 500° C. for 8 hours to obtain a precursor multi-level pore ZSM-5 molecular sieve.

[0066] Step b)

[0067] The materials were re-formulated with the same composition as the above-mentioned synthetic molecular sieve raw material powder, and the total material was reduced to 20%. Tetraethylammonium bromide was used as the template, sodium aluminate was used as the aluminum source, water glass was used as the silicon source, sodium hydroxide was used as the alkali source, and the template was NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - :H2O=0.3:0.01:1:0.1:10, mix the above raw materials and add into the precursor prepared in step a), then stir evenly until it becomes an emulsion and transfer into an autoclave, crystallize at 180°C for 30 hours, wash the synthesized product with water, dry at 120°C for 8 hours, and calcine at 550°C for 6 hours to obtain the desired core-shell ZSM-5 molecular sieve raw powder.

[0068] The core-shell ZSM-5 molecular sieve raw powder is exchanged with a 10% ammonium nitrate aqueous solution at 90°C, washed and dried, and then calcined at 500°C for 8 hours, pressed into tablets, and sieved to obtain a catalyst for cracking carbon four olefins to produce propylene and ethylene. The pore distribution of the catalyst core phase molecular sieve is shown in Table 1. The pore distribution of the catalyst shell phase molecular sieve is: The pore distribution of the catalyst shell phase molecular sieve is: The pore volume occupied by the pores with a pore diameter of less than 2 nanometers is 85% of the total pore volume, the pore volume occupied by the pores with a pore diameter of 2 to 50 nanometers is 5% of the total pore volume, and the pore volume occupied by the pores with a pore diameter of more than 50 nanometers is 10% of the total pore volume. The mass ratio of the catalyst core phase to the shell phase is 5:1.

[0069] The fixed-bed catalytic reaction device was used to evaluate the activity of the prepared catalyst in the cracking of C4 olefins to produce propylene and ethylene. The process conditions used in the investigation were: reaction temperature of 530°C, reaction pressure of 0.02MPa, and C4 hydrocarbon weight space velocity of 15h -1 The evaluation results are shown in Table 3.

[0070] Example 4

[0071] Step a)

[0072] Preparation of ZSM-5 molecular sieve raw powder:

[0073] Tetramethylammonium bromide was used as the template, aluminum nitrate was used as the aluminum source, silica sol was used as the silicon source, sodium hydroxide was used as the alkali source, and the template was NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - :H2O=0.5:0.002:1:0.4:5. The above raw materials are mixed and stirred evenly until they are in an emulsion state, then transferred into an autoclave and crystallized at 120°C for 35 hours. The synthesized product is washed with water, dried at 60°C for 20 hours, and calcined at 500°C for 5 hours to obtain ZSM-5 molecular sieve raw powder.

[0074] Precursor preparation:

[0075] The ZSM-5 molecular sieve raw powder was dispersed in a 5% sodium carbonate solution, stirred at 80° C. for 3 hours, filtered, dried at 120° C. for 8 hours, and calcined at 600° C. for 4 hours to obtain a precursor multi-level pore ZSM-5 molecular sieve.

[0076] Step b)

[0077] The materials were re-formulated with the same composition as the above-mentioned synthetic molecular sieve raw material powder, and the total material was reduced to 25%. Tetramethylammonium bromide was used as the template, aluminum nitrate was used as the aluminum source, silica sol was used as the silicon source, sodium hydroxide was used as the alkali source, and the template was NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - :H2O=0.5:0.002:1:0.4:5, mix the above raw materials and add into the precursor prepared in step a), then stir evenly until it becomes an emulsion and transfer into an autoclave, crystallize at 180°C for 30 hours, wash the synthesized product with water, dry at 120°C for 8 hours, and calcine at 550°C for 6 hours to obtain the desired core-shell ZSM-5 molecular sieve raw powder.

[0078] The core-shell ZSM-5 molecular sieve raw powder is exchanged with a 10% ammonium nitrate aqueous solution at 90°C, washed and dried, and then calcined at 500°C for 8 hours, pressed into tablets, and sieved to obtain a catalyst for cracking carbon four olefins to produce propylene and ethylene. The pore distribution of the catalyst core phase molecular sieve is shown in Table 1. The pore distribution of the catalyst shell phase molecular sieve is: the pore volume occupied by pores with a pore diameter of less than 2 nanometers is 90% of the total pore volume, the pore volume occupied by pores with a pore diameter of 2 to 50 nanometers is 2% of the total pore volume, and the pore volume occupied by pores with a pore diameter of more than 50 nanometers is 8% of the total pore volume. The mass ratio of the catalyst core phase to the shell phase is 4:1.

[0079] The fixed-bed catalytic reaction device was used to evaluate the activity of the prepared catalyst in the cracking of C4 olefins to produce propylene and ethylene. The process conditions used in the investigation were: reaction temperature of 530°C, reaction pressure of 0.02MPa, and C4 hydrocarbon weight space velocity of 15h -1 The evaluation results are shown in Table 3.

[0080] Comparative Example 1

[0081] Tetramethylammonium bromide was used as the template, aluminum nitrate was used as the aluminum source, silica sol was used as the silicon source, sodium hydroxide was used as the alkali source, and the template was NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - :H2O=0.1:0.005:1:0.3:6. The above raw materials were mixed and stirred evenly until they were in an emulsion state, then transferred into an autoclave and crystallized at 150°C for 10 hours. The synthesized product was washed with water, dried at 80°C for 12 hours, and calcined at 600°C for 4 hours to obtain a ZSM-5 molecular sieve.

[0082] The ZSM-5 molecular sieve is exchanged with a 10% aqueous solution of ammonium nitrate at 90°C, washed and dried, and then roasted at 500°C for 8 hours, pressed into tablets, and sieved to obtain a catalyst for cracking C4 olefins to produce propylene and ethylene. In the catalyst, the pore volume occupied by pores with a pore diameter of less than 2 nanometers accounts for 87% of the total pore volume, the pore volume occupied by pores with a pore diameter of 2 to 50 nanometers accounts for 3% of the total pore volume, and the pore volume occupied by pores with a pore diameter of more than 50 nanometers accounts for 10% of the total pore volume.

[0083] The fixed-bed catalytic reaction device was used to evaluate the activity of the prepared catalyst in the cracking of C4 olefins to produce propylene and ethylene. The process conditions used in the investigation were: operating temperature of 530°C, operating pressure of 0.02MPa, and weight space velocity of 15h -1 The evaluation results are shown in Table 3.

[0084] Comparative Example 2

[0085] Tetramethylammonium bromide was used as the template, aluminum nitrate was used as the aluminum source, silica sol was used as the silicon source, sodium hydroxide was used as the alkali source, and the template was NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH -:H2O=0.1:0.005:1:0.3:6. The above raw materials are mixed and stirred evenly until they are in an emulsion state, then transferred into an autoclave and crystallized at 120°C for 35 hours. The synthesized product is washed with water, dried at 60°C for 20 hours, and calcined at 500°C for 5 hours to obtain ZSM-5 molecular sieve raw powder.

[0086] The molecular sieve raw powder was dispersed in a 5% sodium carbonate solution, stirred at 80°C for 3 hours, filtered, dried at 120°C for 8 hours, and calcined at 600°C for 4 hours to obtain a multi-level pore ZSM-5 molecular sieve.

[0087] The multi-level pore ZSM-5 molecular sieve is exchanged with a 10% ammonium nitrate aqueous solution at 90°C, washed and dried, and then roasted at 500°C for 8 hours, pressed into tablets, and sieved to obtain a catalyst for cracking C4 olefins to produce propylene and ethylene. In the catalyst, the pore volume occupied by pores with a pore diameter of less than 2 nanometers accounts for 47% of the total pore volume, the pore volume occupied by pores with a pore diameter of 2 to 50 nanometers accounts for 28% of the total pore volume, and the pore volume occupied by pores with a pore diameter of more than 50 nanometers accounts for 25% of the total pore volume.

[0088] The fixed-bed catalytic reaction device was used to evaluate the activity of the prepared catalyst in the cracking of C4 olefins to produce propylene and ethylene. The process conditions used in the investigation were: operating temperature of 530°C, operating pressure of 0.02MPa, and weight space velocity of 15h -1 The evaluation results are shown in Table 3.

[0089] Comparative Example 3

[0090] Preparation of ZSM-5 molecular sieve raw powder:

[0091] Tetramethylammonium bromide was used as the template, aluminum nitrate was used as the aluminum source, silica sol was used as the silicon source, sodium hydroxide was used as the alkali source, and the template was NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - :H2O=0.1:0.005:1:0.3:6. The above raw materials are mixed and stirred evenly until they are in an emulsion state, then transferred into an autoclave and crystallized at 150°C for 10 hours. The synthesized product is washed with water, dried at 80°C for 12 hours, and calcined at 600°C for 4 hours to obtain ZSM-5 molecular sieve raw powder.

[0092] The materials were re-formulated with the same composition as the above-mentioned synthetic molecular sieve raw material powder, but the total material was reduced to 50%. Tetramethylammonium bromide was used as the template, aluminum nitrate was used as the aluminum source, silica sol was used as the silicon source, sodium hydroxide was used as the alkali source, and the template was NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH- The molar ratio of NH4 to water is: + :Al2O3:SiO2:OH - :H2O=0.1:0.005:1:0.3:6, and 2wt% of methyl cellulose is added as a porogen. After the above raw materials are evenly mixed, the synthesized ZSM-5 molecular sieve raw powder is evenly dispersed in the materials, and after sufficient stirring, it is transferred into an autoclave and crystallized at 150°C for 10 hours. The synthesized product is washed with water, dried at 80°C for 12 hours, and calcined at 600°C for 4 hours to obtain the desired core-shell ZSM-5 molecular sieve raw powder.

[0093] The core-shell ZSM-5 molecular sieve raw powder is exchanged with a 10% ammonium nitrate aqueous solution at 90°C, washed and dried, and then roasted at 500°C for 8 hours, pressed into tablets, and sieved to obtain the desired catalyst for cracking C4 olefins to produce propylene and ethylene.

[0094] The catalyst is a core-shell molecular sieve, the core is a conventional molecular sieve, and the shell is a composite pore structure molecular sieve. The pore distribution of the composite pore structure molecular sieve in the catalyst shell phase is: the pore volume occupied by the pores with a pore diameter of less than 2 nanometers is 35% of the total pore volume, the pore volume occupied by the pores with a pore diameter of 2 to 50 nanometers is 43% of the total pore volume, and the pore volume occupied by the pores with a pore diameter of more than 50 nanometers is 22% of the total pore volume. The pore distribution of the catalyst shell phase molecular sieve is: the pore volume occupied by the pores with a pore diameter of less than 2 nanometers is 87% of the total pore volume, the pore volume occupied by the pores with a pore diameter of 2 to 50 nanometers is 3% of the total pore volume, and the pore volume occupied by the pores with a pore diameter of more than 50 nanometers is 10% of the total pore volume.

[0095] The fixed-bed catalytic reaction device was used to evaluate the activity of the prepared catalyst in the cracking of C4 olefins to produce propylene and ethylene. The process conditions used in the investigation were: operating temperature of 530°C, operating pressure of 0.02MPa, and weight space velocity of 15h -1 The evaluation results are shown in Table 3.

[0096] Table 1 Pore distribution of core phase molecular sieve of catalyst in Examples 1-4

[0097]

[0098] Table 2

[0099]

[0100] Table 3

[0101]

[0102] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalyst for cracking C4 olefins to produce propylene and ethylene, characterized in that: The catalyst has a core-shell structure, the core phase is a ZSM-5 molecular sieve with a composite pore structure, and the shell phase is a ZSM-5 molecular sieve; In the ZSM-5 molecular sieve with a core phase composite pore structure, the pore volume occupied by pores with a pore diameter of less than 2 nanometers is a, the pore volume occupied by pores with a pore diameter of 2 to 50 nanometers is b, and the pore volume occupied by pores with a pore diameter of more than 50 nanometers is c; wherein b / a is 0.10 to 0.80, and c / a is 0.30 to 0.

70.

2. The catalyst according to claim 1, characterized in that The mass ratio of the core phase to the shell phase is 1 to 5:

1.

3. The catalyst according to claim 1, characterized in that In the ZSM-5 molecular sieve with a core phase composite pore structure, the pore volume occupied by pores with a pore diameter of less than 2 nanometers is 20% to 75% of the total pore volume, the pore volume occupied by pores with a pore diameter of 2 to 50 nanometers is 10% to 55% of the total pore volume, and the pore volume occupied by pores with a pore diameter of more than 50 nanometers is 6% to 30% of the total pore volume, preferably 15% to 30%.

4. The catalyst according to claim 1, characterized in that In the shell phase ZSM-5 molecular sieve, the pore volume occupied by pores with a pore diameter of less than 2 nanometers is 85% to 100% of the total pore volume; the pore volume occupied by pores with a pore diameter of more than 50 nanometers is 0 to 15% of the total pore volume; the pore volume occupied by pores with a pore diameter of 2 to 50 nanometers is 0 to 10% of the total pore volume.

5. A method for preparing the catalyst according to any one of claims 1 to 4, comprising the following steps: a) treating ZSM-5 molecular sieve raw powder in alkaline solution and first calcining to obtain a precursor; b) mixing the template, aluminum source, silicon source, alkali source and the precursor in step a), performing hydrothermal crystallization, performing a second calcination, then performing ammonium exchange, and performing a third calcination to obtain the catalyst.

6. The preparation method according to claim 5, characterized in that: The base in step a) comprises at least one of sodium hydroxide and sodium carbonate; And / or, the temperature of the treatment in the alkali solution in step a) is 60 to 100° C., preferably 60 to 90° C.; the treatment time in the alkali solution is 2 to 4 hours; And / or, the first calcination conditions in step a) are: temperature 500-600° C., time 4-8 h.

7. The preparation method according to claim 5 or 6, characterized in that: In step b), The template agent includes at least one of tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide and tetrapropylammonium hydroxide; And / or, the aluminum source includes at least one of aluminum nitrate, aluminum sulfate and sodium aluminate; And / or, the silicon source includes at least one of water glass, silica sol and tetraethyl orthosilicate; And / or, the alkali source includes at least one of sodium hydroxide and potassium hydroxide; And / or, the template is NH4 + The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as OH - The molar ratio of NH4 + :Al2O3:SiO2:OH - : H2O=0.1~0.5: 0.001~0.01: 1: 0.1~0.4: 5~10.

8. The preparation method according to claim 5, characterized in that: In step b), the hydrothermal crystallization temperature is 80 to 200° C., and the crystallization time is 10 to 50 hours; And / or, in step b), the second calcination temperature is 500-600° C. and the time is 4-8 hours; And / or, in step b), the third calcination temperature is 500-600° C. and the time is 4-8 hours.

9. Use of the catalyst according to any one of claims 1 to 4 or the catalyst prepared by the preparation method according to any one of claims 5 to 8 in the cracking reaction of C4 olefins to produce propylene and ethylene.

10. The use according to claim 9, characterized in that: The application is a reaction of cracking low-concentration C4 olefins to produce propylene and ethylene; the low-concentration C4 olefin raw material comes from C4 hydrocarbons in a refinery; in the C4 hydrocarbons, the mass concentration of the C4 olefins is 30% to 50%.

11. The use according to claim 10, characterized in that: The C4 hydrocarbons are C4 mixed hydrocarbons; the C4 mixed hydrocarbons include at least one C4 olefin and at least one C4 alkane; preferably, in the C4 hydrocarbons, the mass concentration of the C4 olefins is 30% to 50%, and the mass concentration of the C4 alkanes is 50% to 70%.

12. The use according to claim 9, characterized in that: The reaction conditions are: reaction temperature of 500-600°C, preferably 520-580°C; and / or reaction pressure of 0-1.0 MPa, preferably 0.03-0.8 MPa; and / or C4 hydrocarbon weight space velocity of 1-30 h -1 , preferably 2 to 20 hours -1 .

Citation Information

Patent Citations

  • Prodn. of olefins

    CN1209443C

  • Prodn. of propylene

    CN1284109A

  • Method for synthesizing core-shell type zeolite molecular sieve

    CN101723402A

  • ZSM-5 composite molecular sieve with a core-shell structure and preparation method and application thereof

    CN103803581A

  • Core-shell type ZSM-5 molecular sieve and preparation and application thereof

    CN104211085A